BERKAH DALAM PERILAKU KONSUMSI MASYARAKAT MUSLIM PERUMAHAN TULUNGAGUNG - Nurohman, Dede (UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
This study aims to reveal the interpretation of the Muslim housing community about the meaning of blessings in their lives and relate it to their consumption behavior, especially in determining the criteria for sellers that contain blessings. This study used a qualitative approach and data mining was carried out using interview, observation and FGD techniques. This study found that their interpretation of blessings was divided into three, namely; blessing as a transcendent value, blessing as a condition, and blessing as a means. In the context of consumption activities, their understanding of the seller's criteria states that the seller's blessing lies with three criteria, namely; sellers who are elderly and serve honestly and friendly, sellers who have the status of students, have the title hajj/hajah, and sellers are male. This finding is expected to provide consideration for the importance of the blessing factor in the formulation of the theory of consumption behavior in Islam.